Apparel exports - still a path for industrial development? Dynamics in apparel global value chains and implications for low-income countries - Cornelia Staritz (Austrian Foundation for Development Research (ÖFSE), 2012)
The apparel sector has traditionally been a gateway to export diversification and industrial development for low-income countries (LICs). In the context of heightened competition and recent changes in the global apparel sector related to trade liberalization and global buyers' sourcing policies, the paper discusses to what extent the apparel sector can still provide this role for LICs today. Recent developments have important implications for LICs that aim to develop through apparel exports, in particular related to (i) increasing entry barriers and global consolidation, (ii) global demand, supply and asymmetric market structures, (iii) high competition in wages and labor standards, (iv) shifting end markets to emerging and regional markets, and (v) the importance of foreign investment with often limited local linkages. The paper concludes that global consolidation and asymmetric market and power structure have increased entry barriers and made upgrading processes more complicated and contested. Even if LIC suppliers fulfill higher requirements and achieve upgrading this does not necessarily secure improved rewards in terms of higher prices, more secure orders and better working conditions. However, shifting end markets to large developing countries, regional and domestic markets, and the increasing importance of developing countries' buyers lead to new opportunities for LIC apparel exporters. Overall, the sector still provides opportunities for industrial development; however, this requires proactive industrial policies in LICs to further upgrading and local value capture as well as a focus away from solely exporting to the US and Europe to regional and domestic markets. At the EU and international level, regulations to secure labor standards and responsible business practices of buyers and changes in the trade and investment regime to increase policy space to support upgrading and industrial development in LICs are necessary.
Keywords: 330; Bekleidung; Export; Internationale Handelspolitik; Wertschöpfung; Bekleidungsindustrie; Entwicklungsländer